A study of Chinese law on restricting personal liberty for public health protection: taking the COVID-19 epidemic as the entry point - Liu, Tengfei; Ma, Zhongwu (Frontiers in Public Health, 2025)
During the COVID-19 pandemic, China adopted restrictive measures such as mandatory quarantine, health code management, and community lockdowns. These actions were effective in containing the epidemic but often lacked clear legal authorization or procedural safeguards, raising concerns about excessive restrictions on personal liberty. From a legal and policy perspective, this paper examines the statutory framework that enabled such measures, focusing on the Law on the Prevention and Control of Infectious Diseases and the Emergency Response Law. It argues that vague authorization and weak procedural constraints left space for local governments to exercise discretionary overreach, exemplified by excessive lockdowns and misuse of digital tools. Building on constitutional principles, the study highlights how legality, necessity, and proportionality should be fundamental limits on emergency powers. It shows that the absence of detailed procedures and rights-protection mechanisms undermined these principles, leading to conflicts between public health and human rights. The paper contributes to Chinese public health law scholarship by clarifying these institutional weaknesses and by proposing reforms to strengthen procedural guarantees, judicial oversight, and regulation of digital surveillance tools. In doing so, it advances understanding of how to balance civil liberties with collective security in future public health crises.